2019
DOI: 10.17161/jas.v5i2.7572
|View full text |Cite
|
Sign up to set email alerts
|

Navigating Role Ambiguity & Conflict: Exploring the Role of the Referee Within the Olympic Sporting Structure

Abstract: This phenomenological study seeks to better understand the role of the referee in the Olympic sporting structure and to deconstruct the apparent dichotomies that exist within this role. Eleven rugby sevens referees each completed a pre-Olympics and post-Olympics interview for a total of twenty-two interviews. From the data, four sources of role ambiguity or conflict emerged: (1) remaining unnoticed vs. media exposure; (2) the team vs. individualistic nature of officiating; (3) being a judge vs. being an athlet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 50 publications
(42 reference statements)
1
1
0
Order By: Relevance
“…Thus, it is vital that sport organizations begin to reframe refereeing as an extension of one's athletic career. A finding supported by this research and previous research on referees (Jacobs et al, 2019;Phillips & Fairley, 2014). Regardless of whether the initial involvement was at seekership, recruitment, closure, or drift stage, the result demonstrated that the perceived environment (i.e., High Stress Environment, Financial Instability) and barriers (i.e., Time, and Lack of Knowledge and Support) all served as obstacles for athletes and led to them not considering or being involved in refereeing.…”
Section: Theoretical Contributionsupporting
confidence: 89%
See 1 more Smart Citation
“…Thus, it is vital that sport organizations begin to reframe refereeing as an extension of one's athletic career. A finding supported by this research and previous research on referees (Jacobs et al, 2019;Phillips & Fairley, 2014). Regardless of whether the initial involvement was at seekership, recruitment, closure, or drift stage, the result demonstrated that the perceived environment (i.e., High Stress Environment, Financial Instability) and barriers (i.e., Time, and Lack of Knowledge and Support) all served as obstacles for athletes and led to them not considering or being involved in refereeing.…”
Section: Theoretical Contributionsupporting
confidence: 89%
“…There are already many referees who consider themselves to be athletes (Jacobs et al, 2019;Phillips & Fairley, 2014); therefore, the similarities between the two roles could potentially be used to recruit athletes into referees. The path from athlete to referee can be facilitated; however, a clear understanding of how athletes perceive the role of refereeing is needed.…”
Section: Referee Recruitmentmentioning
confidence: 99%